2013
DOI: 10.1111/jai.12283
|View full text |Cite
|
Sign up to set email alerts
|

Feeding habits ofSchizothorax oconnoriLloyd, 1908 in the Yarlung Zangbo River, Tibet

Abstract: SummarySeasonal, ontogenetic and sexual feeding habits of Schizothorax oconnori in the Yarlung Zangbo River were studied using percentages by number, weight and index of relative importance (IRI). The Schoener overlap index was applied to compare diets related to season, fish size and sex. The feeding intensity exhibited seasonal trends, with a minimum food intake in summer. Overall, 103 prey taxa belonging to seven prey categories (diatoms, green algae, cyanophytes, other algae, small invertebrates, macroinve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…As also seen in other fishes (Hovde et al 2002;La Mesa et al 2007;Ma et al 2014), the feeding intensity of G. firmispinatus generally followed a seasonal trend. Some studies found that the highest percentage of fish with empty guts occurred during the spawning season, which was attributed to a significant decrease in food ingestion during reproduction (Hovde et al 2002;Šantić et al 2009).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…As also seen in other fishes (Hovde et al 2002;La Mesa et al 2007;Ma et al 2014), the feeding intensity of G. firmispinatus generally followed a seasonal trend. Some studies found that the highest percentage of fish with empty guts occurred during the spawning season, which was attributed to a significant decrease in food ingestion during reproduction (Hovde et al 2002;Šantić et al 2009).…”
Section: Discussionsupporting
confidence: 74%
“…These shifts have also been reported for another species of the Schizothoracinae, Oxygymnocypris stewartii, small individuals of which fed mainly on Cobitidae and Hydropsychidae larvae, while larger individuals tended to consume Cyprinidae and Chironomidae larvae (Huo et al 2014). However, for some other Schizothoracinae fishes (such as Schizopygopsis younghusbandi and Schizothorax o'connori), which have a protruding under jaw with sharp horns and graze mainly on algae, no significant ontogenetic shifts in diets were found (Yang et al 2011;Ma et al 2014). Size-related variations in diet composition possibly reflect morphological and maturational changes, especially an increase in gape size (Graeb et al 2005;Huo et al 2014), improvements in locomotion (Beamish 1978) and sensory capabilities (Li et al 1985).…”
Section: Discussionsupporting
confidence: 53%
“…Most of them are widely recognized as being sensitive to a range of anthropogenic stressors and they are used in the bioassessment of rivers and streams (Atazadeh et al 2007;Sharifinia et al 2012b;Clews et al 2014;Ma et al 2014;Richardson et al 2014).…”
Section: Biotic Indicesmentioning
confidence: 99%
“…The diets of fish were closely related to the environmental characteristics of their habitat, which often varies with spatiotemporal changes (Saikia, 2015). The seasonal changes in fish feeding can be found in most fish species (La et al, 2007;Ma et al, 2014;2020). Compared with spring and winter, summer and autumn have higher water temperatures, faster digestion of prey items, and a shorter retention time of food in the stomach, resulting in higher vacuity rates in summer and autumn.…”
Section: Discussionmentioning
confidence: 99%
“…The stomach content analysis is a traditional method for studying fish feeding, and it is also the most direct and effective. It can accurately determine specific types of diet and is widely used in studies of fish feeding ecology (Yan et al, 2011;Huo et al, 2014;Ma et al, 2014;Sui et al, 2021;Sarker et al, 2023).…”
Section: Introductionmentioning
confidence: 99%